SOME COMMENTS ON THE TERRITORIAL LOCATION OF THE TRIBES THAT LIVED IN THE EARLY IRON AGE IN KHOREZM (Spectrum Journal of Innovation, Reforms and Development, 2023)
The favorable environment for cattle breeding of the ancient Khorezm oasis was the reason for the settlement of nomadic herders from the earliest times. The lower reaches and valleys of the Amudarya often served as villages for cattle herders. In this article is analyzed nomads, which migrated from the north, northeast and north-west in different historical periods. During the Bronze and Early Iron Ages, nomadic herders arrived, adapted to the conditions of this land, and adopted a semi-sedentary lifestyle.